AVICENNA'S INFLUENCE ON MAIMONIDES' "EPISTLE ON ASTROLOGY". Issue 2 (September 2019) - Harvey, Elon
Abstract: This paper shows for the first time that Maimonides significantly relied on Avicenna's "Refutation of astrology" ( Al-Išāra ilā fasād ῾ilm aḥkām al-nujūm ) when composing his own refutation, the "Epistle on astrology" ( ῾Al Gezērat ha-kōkhabīm ). Maimonides consulted a copy of Avicenna's Refutation, partially using its structure as a model for his Epistle, and adapting some of its arguments. Therefore, it may be said with certainty that Maimonides carefully read at least one of Avicenna's works, and that his Epistle is not based solely on his own previous works, the "Commentary on the Mishnah", the "Code of Jewish law", and the "Guide of the perplexed". Résumé: Cet article montre pour la première fois que Maïmonide s'est appuyé de manière significative sur la « Réfutation de l'astrologie » d'Avicenne ( Al-Išāra ilā fasād ῾ilm aḥkām al-nujūm ) pour composer sa propre réfutation, la « Lettre sur l'astrologie » ( ῾Al Gezērat ha-kōkhabīm ). Maïmonide a consulté une copie de la Réfutation d'Avicenne, en utilisant sa structure comme modèle partiel pour sa lettre et en adaptant certains de ses arguments. Par conséquent, on peut dire avec certitude que Maïmonide a lu attentivement au moins une des œuvres d'Avicenne et que sa lettre ne se base pas uniquement sur ses propres œuvres antérieures, le « Commentaire sur la Mishnah », le « Code de la loi juive » et le « Guide des égarés ».